Scheduling Regulated Deficit Irrigation with Leaf Water Potential of Cherry Tomato in Greenhouse and its Effect on Fruit Quality - Leontina Lipan; Hanán Issa-Issa; Alfonso Moriana; Noemí Medina Zurita; Alejandro Galindo; María José Martín-Palomo; Luis Andreu; Ángel A. Carbonell-Barrachina; Francisca Hernández; Mireia Corell (Agriculture, 2021)
The tomato cultivated surface is one of the most important surfaces in the world. This crop needs a sufficient and continuous supply of water during vegetative growth. Therefore, production may be at risk in warm and water-scarce areas. Therefore, the implementation of irrigation alternatives such as regulated deficit irrigation (RDI) is of great importance to reduce the use of water and improve the production of the quality of tomatoes. The objective of this work was to evaluate the deficit irrigation scheduling using plant water status as a tool in deficit irrigation. Experimental design was a randomized design with four replications per treatment. Two irrigation treatments were applied: Control (125% of crop evapotranspiration (ETc)) and Regulated Deficit Irrigation (RDI). This latter treatment considered different threshold values of midday leaf water depending on crop phenological stage. No differences were observed in yield, with RDI treatment being more efficient in the use of irrigation water than the control. Besides, RDI tomatoes presented, in general, greater weight, size, Total soluble solids (TSS), sugars, antioxidant activity, lycopene, β-Carotene, and redder color with more intense tomatoes flavor. Finally, it might be said that RDI strategy helped to reduce 53% of irrigation water and to improve the nutritional, functional, and sensory quality of tomatoes.